Demographic Characteristics and Causes of Low Vision in Children: A Hospital–Based Study from Khartoum, Sudan: Doi: 10.36351/pjo.v37i4.1274 - Alrasheed, Saif Hassan; Awad, Eslah Saeed; Mohamed, Zoelfigar Dafalla (Pakistan Journal of Ophthalmology, 2021)
Purpose: To determine the demographic characteristics and causes of low vision in children who attended Alfaisal eye center, Khartoum Sudan. Place and Duration of Study: Alfaisal eye Center, Khartoum, Sudan, from February 2018 to October 2020. Study Design: Cross sectional observational study. Methods: Clinical record of 105 patients who visited the low vision clinic were retrieved. Demographic features, history, ocular examination, cause of low vision, refractive state of the eye (by self-luminance streak retinoscope, and auto refractometer), and type of low vision devices used by the patients were noted. Data was analyzed by using SPSS software version 20. Results: Mean age was 11.70 ± 2.19. Seventy three percent patients had Visual Acuity(VA) less than 6/60. Majority (59%) were male patients. Commonest refractive error associated with low vision was myopia (65.71%). Retinitis Pigmentosa, congenital glaucoma, and albinism were other major causes of pediatric low vision (19.5%). Progressive Myopia was seen in 15%. About 9.5% of children presented with cataracts, nystagmus in 9.5%, and congenital refractive error in 9.5%.The cause of low vision among children was not statistically different between males and females P=0.890. More than half of the children 78.1% used glasses and about 21.9% were corrected by telescope. Conclusion: Retinitis pigmentosa, albinism, and congenital glaucoma were the most common causes of pediatric low vision. Common low vision devices prescribed to these children were glasses and telescopes. Key Words: Retinitis Pigmentosa, Congenital glaucoma, Albinism, Myopia, Cataract.